Pengaruh Labelisasi Halal dan Preferensi Merek terhadap Minat Beli Kebab Turki Baba Rafi - Uswatun Chasanah; Asri Munzilin; Ach. Agil Dzikrullah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigated the influence of brand preference and halal labeling on customers' desire to buy Baba Rafi Turkish kebabs. Using a purposive sampling approach, 50 respondents were selected as a research sample. Using the Pearson Product Moment correlation method and Cronbach's Alpha technique, the validity and reliability of the research instrument were assessed. Cronbach's Alpha value for the entire instrument is 0.827, which indicates a high level of reliability. All items demonstrate acceptable validity. The impact of independent variables on dependent variables is assessed using linear regression analysis, both collectively and independently. The F test revealed that, taken together, Halal Labeling and Brand Preference had a substantial impact on Buying Interest (F = 5.755; Sig. = 0.006). However, the t-test showed that only Brand Preference had a significant independent effect (t = 3.129 ; Sig. = 0.003 ) , while Halal Labeling did not (t = 0.051 ; Sig. = 0.960). According to the value of the determination coefficient (R2) recorded at 0.197, the two independent variables accounted for 19.7% of the variability in Purchase Interest, while the remaining variance could be attributed to other variables. The conclusion of this study is that brand preference is a major factor influencing consumers' tendency to buy Baba Rafi Turkish kebabs.